Seed Viability, Imbibition Dynamics and Storability of Aegle marmelos (L.) Corrêa: Implications for Propagation and Conservation - MANISH KUMAR VIJAY (Seed Research, 2025)
The present investigation assessed seed viability, water imbibition behavior, pre-treatmentrequirements, and storability of Aegle marmelos (L.) Corrêa. Seed viability, determined through the Tetrazolium(TZ) test, showed significant variation depending on the TZ concentration and staining duration. The highestviability (100%) was observed using 0.5% TZ solution after 4 hours of staining, establishing this combination asoptimal for viability assessment. Imbibition studies revealed a progressive increase in seed fresh weight, followinga characteristic triphasic pattern indicative of physiological readiness for germination. Germination experimentsconfirmed the absence of dormancy in A. marmelos seeds, indicating that no pre-treatment is necessary forsuccessful germination. Storage behavior studies demonstrated that seeds dried to a moisture content of 4.58%and stored at –20°C retained viability above 86% after three months, confirming orthodox storage behavior. Thisfinding contrasts with earlier reports suggesting intermediate seed storage characteristics. Overall, Aegle marmelosseeds exhibit high viability, favorable imbibition dynamics, and excellent storability, supporting their effectiveutilization in propagation and long-term conservation efforts.